Oral morphine analgesia for preventing pain during invasive procedures in non-ventilated premature infants in hospital: the Poppi RCT - Vaneesha Monk (Efficacy and Mechanism Evaluation, 2019)
Background: Identifying better pain management strategies for painful procedures performed in neonatal care is a clinical priority. Retinopathy of prematurity screening and heel-lance blood tests are essential clinical procedures, but adequate pain relief is not currently provided because of a lack of evidence-based analgesia. Morphine provides effective analgesia in older children and adults, but efficacy in infants is controversial. Morphine is, however, commonly used intravenously for sedation in ventilated infants. Objective: The primary objective was to investigate whether or not a single 100 µg/kg morphine sulphate dose administered orally prior to painful clinical procedures provides effective analgesia. Design: Single-centre, prospective, randomised controlled trial. Setting: John Radcliffe Hospital, Oxford, UK. Participants: Thirty-one infants of 34–42 weeks’ gestational age, requiring a heel lance and retinopathy of prematurity screening on the same test occasion. Interventions: The study interventions were 100 µg/kg of oral morphine sulphate (intervention arm) or placebo (control arm) 1 hour before the clinically required procedures. Main outcome measures: There were two co-primary outcomes: Premature Infant Pain Profile-Revised score (a higher score implies more nociceptive processing) during the 30-second period after retinopathy of prematurity screening, and the magnitude of noxious-evoked brain activity (a higher activity implies more nociceptive processing) following the heel lance. Physiological stability and safety were secondary outcomes. Results: After 31 participants were randomised (30 studied and one withdrew), the predefined safety stopping boundary was passed as 3 of the 15 infants who received morphine had apnoeas requiring resuscitation with non-invasive positive-pressure ventilation in the 24 hours after drug administration, compared with 0 of the 15 infants who received placebo [difference in proportion 0.2, 80% confidence interval (adjusted to allow for planned multiple analyses) 0.05 to 1.00; p = 0.085]. The trial was therefore stopped because of profound respiratory adverse effects of morphine without suggestion of analgesic efficacy. There was no significant difference between the trial arms for either primary outcome (Premature Infant Profile-Revised score following retinopathy of prematurity screening mean score ± standard deviation – morphine: 11.1 ± 3.2; Premature Infant Pain Profile-Revised score following retinopathy of prematurity screening mean score ± standard deviation – placebo: 10.5 ± 3.4; mean difference in Premature Infant Pain Profile-Revised score following retinopathy of prematurity screening score 0.5, 95% confidence interval –2.0 to 3.0, p = 0.66; noxious-evoked brain activity following heel lancing median activity – morphine: 0.99, interquartile range 0.40–1.56; noxious-evoked brain activity following heel lancing median activity – placebo: 0.75, interquartile range 0.33–1.22; and median difference in noxious-evoked brain activity following heel lancing 0.25, 95% confidence interval –0.16 to 0.80, p = 0.25). Limitations: The trial lacked power for the primary outcome measures because of early cessation. However, there was a trend across modalities favouring placebo, suggesting that it was unlikely that a clinically significant analgesic benefit would have been detected in the original proposed sample of 156 infants. Conclusions: The administration of 100 µg/kg of oral morphine to non-ventilated premature infants has the potential for harm without analgesic benefit. Oral morphine is not recommended for retinopathy of prematurity screening, and caution is strongly advised if this is being considering for other acute painful procedures in non-ventilated premature infants. Future work: Further clinical trials are essential to ascertain effective pain management for retinopathy of prematurity screening. Using multimodal measures with detailed physiological recordings provides a rigorous approach to assess analgesic efficacy and adverse effects, leading to greater mechanistic understanding of the drug effects. This is essential in future clinical trials of analgesics in infants. Patient and public involvement: The research team worked closely with an on-site charity during the trial design, conduct, oversight and dissemination. Trial registration: Clinical Controlled Trials ISRCTN82342359; EudraCT 2014-003237-25. Funding: This project was funded by the Efficacy and Mechanism Evaluation programme, a Medical Research Council and National Institute for Health Research partnership. Funding was also received for the trial from the Wellcome Trust (reference numbers 095802 and 102076). The report will be published in full in Efficacy and Mechanism; Vol. 6, No. 9. See the National Institute for Health Research’s Journals Library website for further project information.